Label-Free Imaging of Blood Vessels in Human Normal Breast and Breast Tumor Tissue Using Multiphoton Microscopy. (25th June 2019) - Xi, Gangqin; Cao, Ning; Guo, Wenhui; Kang, Deyong; Chen, Zhong; He, Jiajia; Ren, Wenjiao; Shen, Tingfeng; Wang, Chuan; Chen, Jianxin
Abstract : Blood vessels are the important components of the circulatory systems that transport blood throughout the human body and maintain the homeostasis of physiological tissues. Pathologically, blood vessels are often affected by diseases, leading to the formation of unstable, irregular, and hyperpermeable blood vessels. In the tumor microenvironment, abnormal leakage of tumor blood vessels is related to the histological grade and malignant potential of tumors and may also facilitate metastasis of cancer. Visual diagnosis of blood vessels is very important for us to understand the occurrence and development of diseases. Multiphoton microscopy (MPM) is a potential label-free diagnostic tool based on second harmonic generation (SHG) and two-photon excited fluorescence (TPEF). MPM can effectively observe the morphological changes of biological tissues at the molecular and cellular levels. In this work, we demonstrate that label-free MPM can be used to visualize the microstructure of blood vessels in human normal breast and breast tumor tissue. Moreover, MPM can monitor the changes of blood vessels in tumor microenvironment. These results show that the MPM will become a promising technique for clinicians to study the properties of the microstructure of the blood vessels.